TINJAUAN PERKEMBANGAN, KONDISI SOSIAL DAN KREATIVITAS PERAJIN KERAMIK DI KIARA CONDON G BANDUNG - Ayoeningsih Dyah W. (Ars: Jurnal Seni Rupa dan Desain, 2008)
The centre o f the traditional ceramics!pottery industry established in Java spread out across only a fewareas, including Kasongan (Yogyakarta). Plered (West Java), and Kiara Condong (Bandung, West Java).The ceramics/pottery produced by craftsmen o f Kiara Condong possesses unique characteristics; i.e. whiteclay material, low temperature o f burning, and a shiny glazed texture because o f load meni being one o f theingredients.Viewed from the aspects o f shape and pattern o f the ornament, the craftsmen o f Kiara Condong oftenadopt the m otif and ancient decorative style from the Vereenigde Oost-Indische Compagnie (VOC) era and/or o f the Chinese dynasties. The ornamental nature o f the products is not their only distinctive characteristicbut also the unique identity o f ceramics/pottery o f Kiara Condong. The inclination o f the choice o f style andmotif can be considered one o f the efforts in protecting them from the flood o f imported ceramics/pottery.However, some people consider that what they have done is merely copy old creations and that creativityis not required. This phenomenon is worth observing, considering the many factors which became causeo f the problem; such as environmental condition, labour, as well as the high level o f competition betweenfactories (owners).Keyzvords: ceramics/pottery, Kiara Condong, factor, social condition